A reply to calls for an extension of the definition of Sámi in Finland - Aikio, Antti; Åhrén, Mattias (Arctic Review on Law and Politics, 2014)
In Finland the legal definition of the indigenous Sámi has been debated heatedly for years and more recently it has entered academic circles. Some scholars submit that the current law-based definition in Finland is all too narrow, and argue that there should be more emphasis on self-identification by the individual. Further claims state that the ILO Convention No. 169 identifies the subjects of the Convention, also on an individual level; wherefore it follows from the Convention which individuals in Finland are Sámi. The present article analyses these arguments critically and establishes certain legal parameters that the discussion on Sámi definition needs to follow in order to comply with international law, and especially indigenous peoples’ right to self-determination.Keywords: Sámi rights, Sámi definition, ILO Convention No. 169, indigenous peoples’ self-determination, Sámi in Finland.Citation: Arctic Review on Law and Politics, vol. 5, 1/2014 pp. 123–143. ISSN 1891-6252